Optimization Analysis of the Residential Window-to-Wall Ratio Based on Numerical Calculation of Energy Consumption in the Hot-Summer and Cold-Winter Zone of China - Liu, Haiqiang; Zhang, Zhihao; Ma, Xidong; Lu, Weite; Li, Dongze; Kojima, Shoichi (Sustainability, 2021)
Along with the rapid urbanization and economic growth of China over the past decades, the thermal comfort needs of the people in this region have risen dramatically, and at the same time, promoting building energy efficiency is cited as part of the major projects in the 14th five-year plan for energy efficiency improvement. In addition, the outbreak of the COVID-19 epidemic has plunged people into long-term panic, and promoted the entire construction industry to think about a healthier and more sustainable living environment. To respond to the imbalance between energy supply and demand, an optimization analysis based on energy use is developed, assessing the energy efficiency of the window-to-wall ratio (WWR) design and calculating the energy consumption of three different types of residential buildings for both cooling and heating loads as well as for year-round loads. Owing to its harsh climate and huge energy consumption, in this study, the Hot-summer and Cold-winter (HSCW) zone of China was chosen as the experimental setting for the optimization analysis of WWR. Then, in the three main types of residential buildings, including detached houses, multi-story dwellings and high-rise dwellings, a correlation between WWRS and energy consumption in the cooling season, heating season and year-round was built. The comparisons between the WWRS and energy consumption for different types of residential buildings are presented. The design optimization recommendation for WWRS are proposed. It has significant positive meanings for the development of green and sustainably designed residential buildings that offer high levels of thermal comfort and energy efficiency.